2012
DOI: 10.1007/s10750-012-1142-9
|View full text |Cite
|
Sign up to set email alerts
|

Restoring macrophyte diversity in shallow temperate lakes: biotic versus abiotic constraints

Abstract: Although many lake restoration projects have led to decreased nutrient loads and increased water transparency, the establishment or expansion of macrophytes does not immediately follow the improved abiotic conditions and it is often unclear whether vegetation with high macrophyte diversity will return. We provide an overview of the potential bottlenecks for restoration of submerged macrophyte vegetation with a high biodiversity and focus on the biotic factors, including the availability of propagules, herbivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 140 publications
(169 reference statements)
3
154
0
4
Order By: Relevance
“…Especially because the colonisation of fen banks and ponds by seeds is often hampered, either because the propagule bank does not contain many species (Sarneel, 2010;Bakker et al, 2012) or because germination and establishment are hampered (Sarneel & Soons, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Especially because the colonisation of fen banks and ponds by seeds is often hampered, either because the propagule bank does not contain many species (Sarneel, 2010;Bakker et al, 2012) or because germination and establishment are hampered (Sarneel & Soons, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that herbivory by birds decreased macrophyte biomass severely, even up to 100% (Sondergaard et al, 1996;Hilt, 2006;Wood et al, 2012;Bakker & Nolet, 2014), while others found that the removed biomass is compensated by macrophyte regrowth (Mitchell & Wass, 1996;Perrow et al, 1997;Hansson et al, 2010). This apparent contradiction may arise from the varying conditions under which these studies have been conducted, such as the macrophyte and the bird species under consideration, or the experimental set-up (Perrow et al, 1997;Bakker et al, 2013). A recent meta-analysis of all available field studies demonstrated that the impact of herbivory by birds on aquatic plants increases with bird biomass density, offering the first proof that birds systematically reduce macrophyte biomass when present at sufficient densities (Wood et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between charophytes (as submerged macrophytes) and microalgae include a set of known mechanisms, such as competition for inorganic nutrients (Mulderij et al, 2007), allelopathy in both directions (van Donk and van de Bund, 2002;Pflugmacher, 2002), light limitation (Scheffer et al, 1993;Arthaud et al, 2012) and the consequence of shifts in both the size structure and functional roles of the plankton (Bakker et al, 2013), e.g., a decrease in non-edible cyanobacterial filaments (Rojo et al, 2013). Moreover, macrophyte beds offer zooplankton a refuge from fish predation (Burks et al, 2002;Carpenter et al,1985).…”
Section: Introductionmentioning
confidence: 99%